Perspektif Masyarakat Madura tentang Fakta Medis COVID-19 menurut Sosiologi Agama - An-Nisa', Yudita Nuriyah; Fauzi, Agus Machfud (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Everyone's views are different in responding to the COVID-19 pandemic. According to data from the WHO (World Health Organization), the number of people who have died due to COVID-19 has now reached 16.6 million. The main cause of the spread of the corona virus is not implementing health protocols and having a weak immune system or vulnerable age. But not a few people who refuse the provision of vaccination and the application of health protocols as immunization for the body. As a result of the strong religion and culture held by the Madurese community, the assumption is that death is the nature of God, not the result of the corona virus. This is one of the causes of non-compliance in implementing health protocols. The purpose of this study is to see how the Madurese Muslim perspective regarding the medical facts of Covid-19. The method used is a qualitative method with an ethnographic approach. The conclusions and results of this study explain the various perspectives generated by the Madurese Muslim community so that there are those who accept and some who reject the existence of medical facts.